Effects of Institutionalization and Parental Living Status on Children’s Self-Esteem, and Externalizing and Internalizing Problems in Rwanda - Nsabimana, Epaphrodite; Rutembesa, Eugène; Wilhelm, Peter; Martin-Soelch, Chantal (Frontiers in Psychiatry, 2019)
The negative effects of institutionalization on children’s wellbeing have been extensively documented. Throughout the world, particularly in developing countries, many children in orphanages have parents and it is not clear how this situation affects the psychological adjustment of institutionalized children. This study aimed at investigating specifically whether institutionalization impacts negatively children’s psychological adjustment defined in terms of externalizing behavior, internalizing behavior and self-esteem and whether having living parents has additional influence. Using Coopersmith Self-Esteem Inventory and Child Behavior Checklist, data were collected in Rwanda from 6 registered orphanages and 6 primary schools. Ninety-five institutionalized and 82 not institutionalized children aged 9 to 16 participated in the study. For each group we included children whose parents are alive and children without parents. Two, two-way analyses of covariance were performed on externalizing behavior, internalizing behavior and global self-esteem scores while controlling for age and gender. As expected, we found significantly more externalizing problems and lower self-esteem for institutionalized children. Institutionalized children have significantly more internalizing behavior problems when aged 12.63 or bellow. Unexpectedly, having living parents was an aggravating factor among institutionalized children for externalizing behavior and it did not boost their self-esteem. This study provides an important additional understanding in the known effects of institutionalization by highlighting the role of parental living status for the psychological adjustment of these children. This should be considered when developing and improving supportive specific intervention programs for such children and also when making the initial decision to place a child with living parents in an institution.